GAMBARAN BUDAYA KESELAMATAN PASIEN PADA PERAWAT DI RUMAH SAKIT X. BEKASI TAHUN 2022 - Adella Dwi Ayu Ningsih; Ira Marti Ayu; Putri Handayani; Devi Angeliana Kusumaningtiar; Ahmad Irfandi (MOTORIK Jurnal Ilmu Kesehatan, 2023)
The implementation of a culture of patient safety is crucial in hospitals so that patients do not experience unwanted or unexpected hazards during hospitalization. Hospital X. Bekasi has a quality unit, but incident reporting at Hospital X. Bekasi is not going well. This illustrates the implementation of a patient safety culture that is not running well. This study aims to look at the culture of patient safety among nurses in RSX. The year 2022 is seen in the 12 dimensions of the culture of patient safety, according to the Association for Health Care and Research Quality (AHRQ). This research uses a cross-sectional design. The population in this study is the nurse who directly serves the patient. A large sample in this study of 90 nurses was taken with total sampling techniques. The instrument used in this study is the Hospital Survey on Patient Safety Culture (HSOPSC), which has 12 dimensions. The results showed average positive responses from 12 dimensions of patient safety culture (62.5%), Higher Expectations and Action in Promoting Patient Safety (53.3%), Learning for Organizational Continuous Improvement (64.8%), Unit Collaboration (57.5%), Open Communication (61.1), Feedback and Communication on Errors (63.2%), Non-Positive Response (79.6%), Staffing (69.4%), Management Support Dimension for Patient Security (92.2%), Inter-Units Cooperation (64.4%), Overall Perception of Patients Safety (50.2%), Incident Reporting Frequency (50.7%) and Incident Reports Frequencies (50.7%). Hospital X. Bekasi is expected to continue and maintain patient safety programs, evaluate the number of existing staff, improve incident reporting motivation, and conduct comprehensive and periodic patient safety culture measurements.